Does capital regulation matter for bank behaviour? Evidence for German savings banks - Frank Heid; Daniel Porath; Stéphanie Stolz (Deutsche Bundesbank, 2004)
The aim of this paper is to assess how German savings banks adjust capital and risk under capital regulation. We estimate a modified version of the model developed by Shrieves and Dahl (1992). This paper contributes to the literature in three ways. First, we test the capital buffer theory (Marcus 1984, Milne and Whalley 2002). Second, we use dynamic panel data techniques that explicitly take unobserved heterogeneity into account. And third, we provide new evidence for non-US banks by using a new dataset of supervisory data collected by the Deutsche Bundesbank. We find evidence that the coordination of capital and risk adjustments depends on the amount of capital the bank holds in excess of the regulatory minimum (the "capital buffer"). Banks with low capital buffers try to rebuild an appropriate capital buffer by raising capital while simultaneously lowering risk. In contrast, banks with high capital buffers try to maintain their capital buffer by increasing risk when capital increases. These findings support the capital buffer theory.
Keywords: G28; G21; 330; bank regulation; risk taking; bank capital; Sparkasse; Bankrisiko; Eigenkapitalvorschriften; Bilanzstrukturmanagement; Schätzung; Deutschland